A series of 10 malignant triton tumors in one institution. Issue 36 (September 2019) - Bian, Yanyan; Yongbo, Xiang; Xi, Zhou; Zhao, Dachun; Wu, Huanwen; Liu, Yong
Abstract : Abstract: Malignant triton tumor (MTT) is an extraordinarily uncommon and aggressive tumor which have poor prognosis. Malignant peripheral nerve sheath tumors with additional rhabdomyoblasts are found in MTT histologically. The prognosis of patients is poor. The goal of our study is to describe the largest number of cases characteristic and outcome, to our knowledge, such a presentation was not described in the English-language literature until now. From 1999 to 2014, 10 patients (5 women and 5 men) with a malignant triton tumor were treated at our institution. All these cases were followed-up and patient charts were analyzed for outcome. In our study, 3 cases of the Malignant triton tumors originate in the head, 2 cases in the joints, 2 cases in the retroperitoneum, 2 cases in the soft tissues of the thoracic wall, and 1 case in the prostate. Neoplasm associated with pain was the main manifestation. Patients have a poor prognosis. Completely surgical excision of the tumor is the only treatment. Additional radiation or chemotherapy show little effect. Malignant triton tumor is a rare sarcoma. The high probability of developing local recurrence and distant metastases could account for its poor prognosis.